Three tRNA binding sites on Escherichia coli ribosomes. - Rheinberger, H J (1981)
The binding of N-acetyl-Phe-tRNAPhe (an analogue of peptidyl-tRNA), Phe-tRNAPhe, and deacylated tRNAPhe to poly(U)-programmed tightly coupled 70S ribosomes was studied. The N-acetyl-Phe-tRNAPhe binding is governed by an exclusion principle: not more than one N-acetyl-Phe-tRNAPhe can be bound per ribosome, although this peptidyl-tRNA analogue can be present either at the aminoacyl-tRNA (A) site or the peptidyl-tRNA (P) site. Two Phe-tRNAPhe molecules are accepted by one ribosome in the presence of poly(U). This aminoacyl-tRNA binds enzymatically (in the presence of elongation factor Tu and GTP) and nonenzymatically to the A site and is then transferred to the P site, if that site is free. If this elongation factor G-independent movement is hampered, either by using an incubation temperature of 0 degrees C or by the addition of the translocation inhibitor viomycin, only one Phe-tRNAPhe per ribosome can be bound. The effect of the peptidyltransferase inhibitor chloramphenicol on the binding is similar to that of viomycin. In the absence of poly(U), Phe-tRNAPhe cannot bind to the ribosome. Deacylated [14C]tRNAPhe can bind in three copies to one ribosome. The new third tRNA binding site is called the "E" site. The sequence of filling the sites is P, E, and A. The apparent binding constants for the P and the E sites are both approximately 9 X 10(6) M-1 and that for the A site is 1.3 X 10(6) M-1. In the absence of poly(U), only one deacylated tRNAPhe can be bound per ribosome. This tRNAPhe most likely occupies the P site.